EFFECT OF FINANCIAL RISK ON PROFITABILITY OF DEPOSIT MONEY BANKS IN NIGERIA - Aliyu, Abdulrazak Mohammed; Onumoh, Yahaya Ahmed; Monira, Nurjahan Akter; Onmonya, Lucky; Dangs, Ayuba Zakka (International Journal of Accounting & Finance Review, 2025)
Financial risks have significantly impacted the profitability of deposit money banks (DMBs), particularly through operational and solvency risks. Traditional operational pitfalls, coupled with challenges in compliance and environmental disturbances, contribute to operational risks that jeopardize the stability of the banking system. Solvency risks pose a threat to the sustainable operation of commercial banks when they are unable to meet their debt obligations. These financial risks lead to a decline in financial performance, as they result in increased costs, reduced revenues, and a loss of stakeholder trust. Addressing these issues is crucial for improving the financial returns of Nigerian DMBs and maintaining strong foundations in their evolving financial sector. This research investigates the impact of financial risks on the profitability of Nigerian-listed deposit money banks. Return on assets is used as the measure of profitability, while operating risk and solvency risk serve as proxies for financial risk. The study employs an ex post facto research design and gathers data from the audited annual financial reports of 11 listed deposit money banks from 2014 to 2023. The results show that operating risk has a positive and statistically significant effect on profitability, highlighting the importance of effective operational risk management. In contrast, solvency risk shows an insignificant effect on profitability. The findings suggest that effective financial risk management is essential for safeguarding profitability and ensuring sustainable operations for Nigerian DMBs within a competitive and turbulent economic environment. JEL Classification Codes: G21, G32, G15, E44, L25.